Dry Ruderal Habitats and Plant communities of the Uohod Mountain region of Madinah, Saudi Arabia - AL mahdi, Fahad mohammad; AL Sheikh, Mohammed Abdul Raouf (Journal of agricultural, environmental and veterinary sciences, 2019)
Vegetation Study of research area included three different dry environments in Mount Uhud at Medina, Kingdom of Saudi Arabia. Environments located in North Area, Valley Bridge, and East Area Environment. The study results revealed that vegetation study composed of 85 vegetation type affiliated with 78 kind belong to 30 species. There are eight types of annual plants and 4 types of perennials. Annual the plants from vegetation study of research area were 58 %, dwarf shrubs were 25%, shrubby plants were 12%, and perennials were 5%. and 1% of the shrubby plant. Eleven plant populations in research area is determined and merged as well as collected in five main groups and count the dominant species in each population In order to reach the new environments and clans which is VG (I): Acacia hamuosa- Ochradenusbaccatus: VG (II):Acacia tortilis-Trichodesma Africana VG (III): Tribulusmacropterus - Tetrina simplex- Aervajuvanca VG (IV): Atriplexsuberecta-Amaranthusgraecizans. VG (V): Lepidiumaucheri – Trigonellahamosa.